(untitled) (Physical Education, Health and Social Sciences, 2025)
The current study is focused on identifying the relation between cigarette smoking and cardiovascular risk among middle aged adults (30 to 60 years). A cross-sectional survey was utilized to collect data from 200 patients with cardiac issues seeking treatment at various cardiac preventive unit of twin cities (Rawalpindi & Islamabad) of Pakistan. Cigarette dependence was evaluated with the Cigarette Dependence Scale-12 (Jean-François Etter, Thanh Vu Duc & Thomas V. Perneger, 2003) and the Framingham Risk Score (Peter et al., 1998) assessed the risk of cardiovascular diseases of the study participants. The results revealed that a significant correlation exist between smoking cigarette and cardiovascular risk (r = 0.866, p < 0.001). The level of dependence on cigarettes strongly predicted a person’s cardiovascular risk score (β = 0.059, p < 0.01). Cigarette smoking was found to play a significant part in heightening cardiovascular risk for middle-aged adults. To lower burden of CVD in this group, tobacco cessation programs are needed. Public health plans should link smoking cessation with standard cardiac checkups.